Indonesia’s Municipal Solid Waste 3R and Waste to Energy Programs - Farizal, Farizal; Aji, Radityo; Rachman, Amar; Nasruddin, Nasruddin; Indra Mahlia, Teuku Meurah (Makara Journal of Technology, 2017)
Like most cities in the world, population in Indonesia continues to grow every year. Problems that can arise from this are the increasing amount of municipal solid waste (MSW) production and the growing demand for electricity. To deal with the problems, Indonesian government runs 3R (Reduce, Reuse and Recycle) and WTE (Waste to Energy) Programs simultaneously. 3R program aims to reduce the number of waste, while WTE program aims to generate electricity as an alternative energy source. This study aims to find out the optimal proportion of MSW treated through the 3R and WTE programs. For the purpose, a goal programming model has been developed and solved using LINGO 11. The results showed that the optimal proportion of MSW through the 3R program is 49.90%, 12.37% through WTE program. This leaves 37.73% of waste untreated. The electricity generated from WTE program reached 1,229.695 GWh, total emissions that can be saved is 1,809,208.2 tons CO2 equivalent and total land-use for the programs is 4,036,239.1 m2. This study was enriched by performing some scenarios, i.e. adding budget allocation of WTE program, tightening the limit of total emission from waste management and reducing the limit of land-use for waste treatment.